Stratigraphic-Tectonic Evolution and Characterization of the Carboniferous in the Karamay–Baikouquan Fault Zone in the Northwestern Margin of the Junggar Basin, Northwest China - Ma, Yinshan; Wang, Tao; Yang, Yazhou; Liu, Zhiwei; Zhang, Lei; Bai, Yu (Frontiers in Earth Science, 2022)
The northwestern margin of the Junggar Basin has a complex tectonic history, which is challenging for hydrocarbon exploration. This study highlights the structural patterns, tectonic evolution, and controlling factors of the Karamay-Baikouquan Fault Zone (KBFZ) in the northwestern margin of the Junggar Basin based on well log and 3D seismic data. The main findings of this study include: ① Spatially, we have divided the structural patterns of KBFZ into three zones in plan view, namely northern, central, and southern zones; temporarily, the tectonic evolution has been divided into five stages from Late Carboniferous to Cretaceous, namely Early-Middle Carboniferous, Late Carboniferous-Early Permian, Middle-Late Permian, Triassic-Middle Jurassic, Late Jurassic-Cretaceous. ② During the Hercynian and Indochina orogeny, the compressional stress from the movement of the Dalabute strike-slip fault and the Genghis-Junggar strike-slip fault produced various degrees of deformation in different locations in the KBFZ. The general structural style is a mixture of strike-slip and thrust-nappe. The main controlling factors include stress period, stress direction, and stratigraphic-lithologic associations. This study has implications for hydrocarbon exploration and development in the northwestern margin of the Junggar Basin.